THE STABILITY OF THIOSULFATE IN THE PRESENCE OF PYRITE IN LOW-TEMPERATURE AQUEOUS SOLUTIONS - Yong X.; Schoonen M.A.A. (My University, 1995)
The decomposition rate of thiosulfate (S2O2-3) and the formation rates of its partial decomposition products, sulfite (SO2-3), sulfate (SO2-4), and tetrathionate (S4O2-6), were measured in the absence and presence of pyrite in aqueous solution of pH 2.9-8.6 at 20°C. The pyrite-surface-catalyzed oxidation of S2O2-3 to S4O2-6 by dissolved oxygen is the dominant S2O2-3 decomposition mechanism under the experimental conditions.The rate of tetrathionate formation is first order with respect to the pyrite surface concentration and has a fractional order (0 =< n =< 1) with respect to the S2O2-3 concentration. This result is consistent with a surface-controlled heterogeneous mechanism and can be fitted with a Langmuir-Hinshelwood rate equation. The rate shows no pH dependence in the pH range between 2.9 and 6.6, but decreases in alkaline solution. The catalysis of pyrite in this reaction originates from its strong affinity for aqueous sulfur species and its semiconducting properties. Pyrite is thought to form an interfacial intermediate complex with the aqueous electron donor, S2O2-3, on anodic sites, and the terminal electron acceptor, O2, on cathodic sites. The electrons can transfer from the anodic site to the cathodic site via the conduction band of pyrite. In essence, the presence of pyrite eliminates a symmetry mismatch between the frontier orbitals of thiosulfate and oxygen. In the absence of pyrite, this symmetry overlap precludes the progress of this reaction and thiosulfate decomposes via disproportionation to yield sulfite and elemental sulfur.